Neo-epitopes emerging in the degenerative hippocampal granules of aged mice can be recognized by natural IgM auto-antibodies. Issue 1 (December 2015) - Manich, Gemma; Augé, Elisabet; Cabezón, Itsaso; Pallàs, Mercè; Vilaplana, Jordi; Pelegrí, Carme
Abstract Background Degenerative granular structures appear progressively with age in the hippocampus of most mouse strains. We recently reported that these granules contain a neo-epitope that is recognised by IgM antibodies present as contaminants in many commercial antibodies obtained from mouse ascites and mouse or rabbit serum. We hypothesise that these anti-neo-epitope IgMs are in fact natural auto-antibodies that are generated spontaneously during the foetal stage without previous contact with external antigens and whose repertoire and reactivity pattern have been determined through evolution, being remarkably stable within species and even between species. Findings In the present work we found that mice from the ICR-CD1, BALB/C and SAMP8 strains have anti-neo-epitope IgM antibodies in their plasma at all ages tested and even when maintained under specific opportunistic pathogen-free conditions. Moreover, we determined that these anti-neo-epitope IgMs are also present in rabbit, goat and rat serum. We also found that, in each mouse that presented hippocampal granules, the anti-neo-epitope IgMs contained in its plasma recognised the neo-epitopes in its own granules. Conclusions This study led to the conclusion that anti-neo-epitope IgMs are widespread natural auto-antibodies contained in the plasma of mice and other species. The presence of these natural auto-antibodies not only explains why they are frequently found as contaminants in commercial antibodies, but also paves the way for a new approach to a treatment and diagnosis of pathological brain processes based on natural IgMs and neo-epitopes.